Application Of A Scientific Approach To Improve Learning Outcomes In The Mini Volleyball Game (Classroom Action Research on Grade VI Students of SD Negeri 72 Lubuklingau Academic Year 2022/2023) - Adiputra, Ahmad Mahendra; Simamora, Hotlider H (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The aim of this research is to apply a scientific approach to improve learning outcomes in the game of mini volleyball for class VI students at SD Negeri 72 Lubuk Linggau in 2023. Classroom Action Research uses an approach that lasts 2 cycles, each cycle has one meeting consisting of planning, implementing actions, observing and reflecting. The research subjects were 32 students in class V I of SD Negeri 72 Lubuklinggau , with 15 male students and 17 female students . While the data collection methods used were observation and performance tests, data processing used descriptive percentages. Student learning outcomes increased in cycle I with an average score of 68 and increased in cycle II with an average student score of 83. Likewise, the percentage of students who succeeded in each cycle also increased. With a percentage of success results of 47% (15 students) in cycle I then 94% (30 students) in cycle II. Thus, it can be concluded that the scientific approach can improve the learning outcomes of the mini volleyball game in class V I students at SD Negeri 72 Lubuklinggau in the 2022/2023 academic year . The suggestion is that a scientific approach should be an alternative choice in playing mini volleyball for physical education and health teachers.